The Implementation of a Differentiated Approach to Improve Collaboration Skills in Physics Material - Sopacua, Fryan (Journal of Science and Science Education, 2025)
Students often face difficulties in socializing with their peers during the learning process. Therefore, a learning approach that can enhance collaborative skills is needed—one such approach is differentiated instruction. This study aims to describe students' collaboration skills through the implementation of a differentiated approach in learning physics at Grade X of SMA B in West Seram Regency. The subjects of this study were 26 students from class X-2 at SMA B. The research employed a descriptive quantitative and qualitative method. The experimental design used was a one-shot case study. The instrument used in the study was non-test-based, namely an observation sheet designed to measure collaboration skills. Data analysis was conducted using quantitative descriptive analysis to present the data in percentage form, as well as qualitative descriptive analysis to explain the findings through narrative descriptions. The data analysis techniques included both qualitative and quantitative descriptive analysis, which involved observing students’ collaboration skills using the differentiated approach. The observation sheet results showed that students’ collaborative skills reached a percentage of 72.43%, which falls under the high category. This high category was attributed to the fact that learning through a differentiated approach enabled students to demonstrate improved collaboration skills—such as active participation, responsibility, flexibility and compromise, and mutual respect.